Ricebean: High valued fodder crop - Singh, Magan; V, Rundan; Onte, Santosh (Indian Farming, 2020)
From the above facts, ricebean is a vibrant potential fodder legume crop which has the capacity to enhance the productivity and quality of fodder to the livestock and sustain under wide of range climatic conditions.